Pengaruh Kualitas Pelayanan, Persepsi Harga, Dan Kualitas Produk Terhadap Kepuasan Pelanggan Pada Sendy’s Swalayan Palangka Raya - Nadia Putri Permata Ray Bimaria; Murie P. Kulu; Peridawaty Peridawaty (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2020)
Purpose, - This study aims to determine the effect of service quality, price perception and product quality on customer satisfaction at Sendy’s Swalayan Palangka Raya.Design/methodology/approach - The research method uses an explanatory approach to techniques survey, the number of samples in this study were 100 respondents, the sampling technique using census techniques. Data collection methods using questionnaires and documentation studies, while data analysis techniques used in this research are descriptive analysis techniques and multiple linear analysis techniques. Findings - The results showed that the influence of service quality, price perception and product quality on customer satisfaction at Sendy’s Swalayan Palangka Raya. And the results of the descriptive analysis state that the respondents agreed with the proposed indicators.